Evaluation of Supplementary Feeding (PMT) of Mung Bean Biscuits in Ced Pregnant Women - Baluntu, Zulaeha; Ahmad, Mardiana; Hadju, Veni; Handayani Idrus, Hasta (Journal of Neonatal Surgery, 2025)
Introduction The global prevalence of chronic energy deficiency (CED) in third trimester pregnancy is 35-75%.. Methode The method of research was literature review based on national and international scientific journals on the evaluation of supplementary feeding of mung bean biscuits in pregnant women with chronic energy deficiency. Publications between 2019-2024 on PubMed, Google Scholar, and Semantic databases using Indonesian English keywords. “chronic energy deficiency” in pregnancy”,“mung beans”, “vigna radiata”, There were 105 articles identified. Furthermore, screening was carried out to get 68 articles, then selected abstracts, full text, open access and type of research obtained 40 eligibility articles. The final process is to read and select eligibility articles based on the criteria obtained 30 relevant articles consisting of 5 international articles and 25 national articles. Result The literature search results obtained thirty literature related to the evaluation of mung bean biscuit supplementation in chronic energy deficiency pregnant women. The result of the literature search found that the supplementary feeding programme for chronic energy deficiency pregnant women can overcome the problem of chronic energy deficiency by increasing the upper arm circumference. Mung beans can be used as a basic ingredient for making local food products. Mung bean biscuits for chronic energy deficient pregnant women on labour outcomes are still very limited in the research literature. Conclusion The mung bean has complete nutrients both macro and micro nutrients needed by pregnant women who experience chronic energy deficiency. Making supplementary food with mung beans is proven to help improve the nutritional status of chronic energy deficiency pregnant women.